RETRACTED: Measuring Energy Efficiency Performance in China: Do Technological and Environmental Concerns Matter for Energy Efficiency? - Chen, Xue; Liu, Zhen; Saydaliev, Hayot Berk; Abu Hatab, Assem; Fang, Wei (Frontiers in Energy Research, 2021)
In light of the significance of green governance in economic restructuring and the green technology revolution, this study examines the impact of China's recent green governance policies and their implications in various regions; it also examines new models, methods, and development directions for China's green governance in the future. Green governance efficiency and spatial patterns have been studied through 2008-18 data using a three-stage generalized panel Data Envelopment Analysis (DEA) model, spatial autocorrelation model, spatial gravity model, and social network analysis. The study summarizes the status and role of each provincial region in green governance based on the social network of green governance efficiency under the network architecture. It concludes that (i) green governance efficiency in China's provinces has a U-shaped trend, with non-managerial elements in the external environment masking genuine green governance efficiency. (ii) During the study period, the overall efficiency of the industrial system improved. The efficiency of the manufacturing and wastewater stages has been substantially enhanced, but no significant gains were observed in the treatment stages of solid and gas waste. (iii) Although China has made progress in enhancing the overall efficiency of its industrial system, there is still potential for improvement. (iv) China has established a "three horizontal and two vertical grid-type" green governance spatial correlation structure among the sub-stages of the industrial system, and the radiation impact of major provincial areas would increase overall green governance efficiency.